Lixiviats Issus De La Decharge Publique De La Ville De Meknes : Caracterisation Et Impact Sur Les Eaux De L’oued Boufekrane - Hicham, Lekehal; Aziz, Bouchelta; Brahim, Benzougagh; Roukia, Boukhari Taleb (European Scientific Journal, ESJ, 2018)
Leachate from the public landfill of the city of Meknes is considered as a source of significant pollution of the waters of the Boufekrane wadi and agricultural land bordering the landfill. The objective of this study is the characterization of the physicochemical parameters of the leachates as well as the determination of the degree of pollution of the local superficial waters in order to propose adequate techno-economic solutions to remedy this problem. The results obtained following the characterization of the leachates showed that they represent a very important salinity (electrical conductivity: 30805μs / cm) with a strong organic and mineral pollutant load (BOD5: 598mg / l, COD: 3346mg / l and Chlorides: 5144mg / l) .Water quality monitoring in Boufekrane Oued has shown that the qualities are poor and that the contents of the majority of the parameters analyzed are well above the limit values for direct discharges into the receiving environment (EC: 9642μs / cm, COD: 910mg / l, BOD5: 320mg / l, dissolved oxygen: 7.2mg / l, Chlorides: 4470mg / l, Sulphates: 435mg / l). The principal component analysis confirmed that the results obtained are very consistent and consistent with the descriptive analysis.